Specialized Pro-Resolving Mediators Mitigate Cancer-Related Inflammation: Role of Tumor-Associated Macrophages and Therapeutic Opportunities - Lavy, Margot; Gauttier, Vanessa; Poirier, Nicolas; Barillé-Nion, Sophie; Blanquart, Christophe (Frontiers in Immunology, 2021)
Inflammation is a fundamental physiological response orchestrated by innate immune cells to restore tissue homeostasis. Specialized pro-resolving mediators (SPM) are involved in active resolution of inflammation but when inflammation is incomplete, chronic inflammation creates a favorable environment that fuels carcinogenesis and cancer progression. Conventional cancer therapy also strengthens cancer-related inflammation by inducing massive tumor cell death that activate surrounding immune-infiltrating cells such as tumor-associated macrophages (TAM). Macrophages are key actors of both inflammation and its active resolution due to their plastic phenotype. In line with this high plasticity, macrophages can be hijacked by cancer cells to support tumor progression and immune escape, or therapy resistance. Impaired resolution of cancer-associated inflammation supported by TAM may thus reinforces tumor progression. From this perspective, recent evidence suggests that stimulating macrophage’s pro-resolving functions using SPM can promote inflammation resolution in cancer and improve anticancer treatments. Thus, TAM repolarization toward an antitumor phenotype by using SPM opens a new line of attack in cancer treatment. Here, we review SPM’s anticancer capacities with special attention regarding their effects on TAM. We further discuss how this new therapeutic approach could be envisioned in cancer therapy.